A Herpes Simplex Virus Type 2 Variant in which a Deletion across the L-S Junction Is Replaced by Single or Multiple Reiterations of Extraneous DNA - Harland, June; Brown, S. Moira (Journal of General Virology, 1989)
SUMMARY We have isolated and characterized a novel variant of herpes simplex virus type 2 (HSV-2) strain HG52 which has a deletion of 13·5 kb across the L–S junction of the genome, resulting in all of the IRL region, half of the IRS region and the intervening L-S junction ‘a’ sequence(s) being removed. The deleted DNA has been replaced by single or multiple (up to 14) reiterations of a DNA sequence approximately 1 kb in length. Individual genomes within the population range in size from approximately 12 kb smaller than unit length to unit length or marginally larger. The L component of the genome is fixed in the prototype orientation while the S component inverts inefficiently. The variant is viable in tissue culture, is not temperature-sensitive, demonstrates impaired single-cycle growth characteristics and, apart from altered mobility of a single species (29.5K), its polypeptide profile in infected cells appears normal. Southern blot analysis has failed to identify the inserted sequences as being derived from HSV-2.
Keywords: deletion variant